Analysis of finite frequency selective surfaces backed by dielectric substrate using sub-entire-domain basis function method. Issue 4 (6th July 2015) - Wang, Quan-Quan; Zhu, Hong-Bo; Chen, Ru-Shan; Hu, Yun-Qin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Analysis of the frequency selective surface (FSS) is of great significance. In the method of moments, when the electric size of the FSS increases, huge in-core memory and CPU time are required. The purpose of this paper is to efficiently analyze the finite FSS backed by dielectric substrate utilizing sub-entire-domain (SED) basis function method. Design/methodology/approach – Different types of SED basis functions are generated according to the locations of the cells in the entire structure, and a reduced system is constructed and solved. The couplings of all cells of the FSS are taken into account by using Green's function and Galerkin's test procedure. The spatial Green's function is obtained with the discrete complex image method. The reflection and transmission coefficients of the FSS are calculated using the far field of the FSS and the metallic plate with the same size. Findings – Moderate problems of the finite FSS backed by dielectric substrate are solved with the SED basis function method. The original problem can be simplified to two smaller problems. It enables a significant reduction to the matrix size and storage, and efficient analysis of FSS can be performed. The band-stop type of FSS can be composed of periodic conductive patch cells on the dielectric substrate, and shows total reflection property at the resonant frequency. Originality/value – The SED basis function method is mostly used to analyze periodic PEC structures in free space. The layered medium Green's function is successfully employed and several dielectric substrate backed finite FSSs are discussed in this paper. The calculation of reflection and transmission coefficients, which are more effective rather than far field scattering of the FSS, are described.